UPAYA MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INDONESIA MELALUI PENERAPAN METODE DEBAT PADA SISWA KELAS V SDN 09 MATTEKKO KECEMATAN BARA KOTA PALOPO - Ni’ma Zainuddin (Pedagogik Journal of Islamic Elementary School, 2018)
The research by using the method of debate aims to improve speaking skill on the students of grade V SDN 09 mattekko. This type of research is classroom action research (CAR). The subjects were teachers and students of class V SDN 09 Mattekko Kecamatan Bara Palopo city which amounted to 24, 10 men and 14 women. Research kurt lewin model has four stages of planning, implementation, observation, and reflection. Data collection using objective test method, that is by measuring students' speaking skills and observation method using observation sheet which aims to observe student activity and guidance. Qualitative and quantitative approaches are used to analyze collected data. From the research result of debate method can improve speech skill of class V student SDN 09 Mattekko. This is addressed by an increase in the average value. The number of students reaching the minimum criterion score (MCS) on the preeclosure test is 29.17%, the first cycle is 58.33%, and the second cycle is 95.83%. While the average value of pratindakan 63.75, 68,09 cycle I, and cycle II 77.33. Success in this process can be seen from the liveliness and enthusiasm of students in following the process of learning activities, in this case, students have dared to issue ideas and respond to any existing answers and questions from opposing groups. Keywords: